Law and the constitution - Jennings, Sir Ivor. (London, 1976)
THE LAW AND THE CONSTITUTION is a standard work concerned with fundamental ideas which discusses the relationship between government and the law in the modern constitution.
Keywords: Great Britain-Constitution